Solar Panel Light Intensity and Voltage Measurement System Using Atmega 328 - Pane, Rangga Rio Pratama; Sri Nengsih, Sri Nengsih (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
This research explores the development of a real time measurement system for light intensity and voltage in solar panels It utilizes the ATmega328 microcontroller with an INA219 sensor for voltage measurement a BH1750 sensor for light intensity measurement and a logger module The objective of this research is to assist and reduce losses in the use of solar panels The research method is a simplified version of the 4D model reduced to 3D: define design and develop This system is designed to accurately collect data directly from solar panels with a recorded data error rate of 23 The gathered data is stored via an SD card on the logger module and converted into CSV text format Test results indicate that this system can measure accurately and store data in a readily accessible and processable format ATmega328 as the system s core allows accurate real time monitoring of solar panel conditions while storing data in CSV format facilitating further analysis Therefore this system can be a valuable tool for monitoring and enhancing the energy efficiency produced by solar panels < p>